Examen Especial al Proceso de Contratación Pública para el Proyecto Ecoturístico Chorro Viringo del Gobierno Autónomo Descentralizado Municipal de Piñas, provincia de El Oro, periodo fiscal 2021 – 2022. - Valarezo Ruiz, Guissela del Carmen (2023)
In accordance with the stated objectives, the conducting of a Special Examination of the Minor Public Procurement Process for Works of the Ecotourism Project 'Chorro Viringo,' carried out by the Municipal Autonomous Government of Piñas, El Oro province, during the periods of 2021 and 2022, allowed for the verification of compliance with the Organic Law of the National Public Procurement System, its regulations, and codification. The methods and research techniques applied in the research work allowed for the collection of the most relevant and necessary information for the implementation of the special examination. A comparison was made between the process promulgated and the budget published and awarded by the entity within the SERCOP public procurement portal, applying an internal control evaluation to the examined component allowed for the verification of the proper execution of this process. Therefore, through this examination, the main results obtained regarding the analyzed component are as follows: the lack of accessible documentation within the public procurement portal and a record of the Public Deed beyond the established term resulted in a low level of risk and a high level of trust. This also led to non-compliance with current legal regulations, impeding the proper execution of the contract. Therefore, the final audit report presents the relevant findings expressed through comments, conclusions, and recommendations.